Agricultural R&D in West Asia and North Africa: Recent investment and capacity trends - Stads, Gert-Jan (International Food Policy Research Institute, 2015)
This report assesses trends in investments and human resource capacity in agricultural R&D in WANA, focusing on developments during 2009–2012. The analysis is based on information from a set of country factsheets prepared by the Agricultural Science and Technology Indicators (ASTI) program of the International Food Policy Research Institute, using comprehensive datasets derived from primary surveys targeting over 300 agencies in 11 countries during 2013–2014. Accounting for about two-thirds of the region’s total agricultural gross domestic product (AgGDP), the 11 sample countries do not provide a complete overview of agricultural R&D expenditures and staffing in the region as a whole. Yet, these countries are representative of the region’s diversity in terms of income level, country size, and agroclimatic characteristics.